Pengaruh Independensi dan Pengalaman Kerja terhadap Kualitas Audit pada Kantor Akuntan Publik di DKI Jakarta Timur - Utina Kobak; Eka Budi Yulianti; Rosaidah Permana Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to test and determine how important the influence of Independence and Work Experience is on audit quality at Public Accounting Firms (KAP) in East Jakarta. The research method used is quantitative because it has conducted tests using SPSS such as respondent identity, gender, age, last level of education, length of service and also conducted classical assumption tests, namely data validity, data reliability, data linearity, multicollinearity, heteroscedasticity, autocorrelation test, simple linear regression, multiple linear regression, coefficient test, correlation coefficient test and also partial and simultaneous hypothesis tests. This study proves that the influence of independence and work experience as variables that are very influential, an auditor must have these two integrities with a responsible basis in order to provide good and quality audit results.